Contemporary Muslim Women In Northern Nigeria: Challenges and Prospect - Aisha Balaraba Bello; Faiza Kabir Umar; Muhammad Garba Wakili (Journal Al-Muqaddimah, 2024)
Contemporary Muslim women in Northern Nigeria are facing numerous challenges in their social, educational, behavioral, and cultural development within their respective societies. The challenges faced by Muslim women in Northern Nigeria have emerged and escalated due to the gradual adoption of Western culture and civilization facilitated by modern technological advancements. These changes have not occurred by chance; rather, they have been influenced by various factors, including Western biases against Muslim women and a lack of awareness and understanding of Islamic teachings among some Muslim women. These teachings are crucial for safeguarding the sanctity of Muslim women and the entire Muslim Ummah in Northern Nigeria and the wider world. The findings of this paper highlight the behaviors and challenges experienced by contemporary Muslim women in Northern Nigeria, which have led to a decline in their moral values within the religious context, their pursuit of Western education, and their cultural norms. This paper will also offer evidence of certain social issues that some Muslim women have adopted, while further elucidating the status and role of Muslim women in Islam. However, it’s important to note that the methodology employed in this paper is solely explanatory in nature.